THE RIGHT TO GOOD ADMINISTRATION AS A CONSTITUTIONAL RIGHT OF THE PERSON: EU EXPERIENCE - Tetyana Kaganovska; Vitalii Serohin (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. The research of domestic lawyers in the field of good governance is largely focused on the organization of the public power apparatus, while the "human dimension" mostly remains outside the boundaries of scientific discourse, which does not correspond to the challenges facing Ukraine in the context of European integration of work. In general, reforms in the field of public administration should receive a clearer humanistic orientation, for which it is necessary to translate them into the plane of the legal status of a person. One of the important tasks on this path is the adoption into the national legal system of the right to proper administration, enshrined in the Charter of Fundamental Rights of the EU. Such a reception requires a proper doctrinal basis. The purpose of this article is to determine the right of legal nature to proper administration, its content and scope, its place in the system of fundamental rights of a person, as well as its relationship with the concepts of appropriate management and proper administration.